SEMANTIC AND PRAGMATIC IMPAIRMENTS OF PERSON WITH ALZHEIMER’S DISEASE - Zuyyina Qonita; Rohmani Nur Indah (LUNAR, 2023)
Understanding Alzheimer's disease affecting the communication ability can be done through investigating the language impairment of the sufferers. Therefore, this study aims to analyze the language impairments of person with Alzheimer’s disease as represented in The Father movie. It focused on the semantic and pragmatic impairment in the speech produced by Anthony as the main character with Alzheimer’s disease. Qualitative method is employed to get a deep understanding of the language impairments. The findings of this study indicated that the types of semantic impairments found are: errors in verbal fluency, difficulty in word comprehension, empty speech, word retrieval difficulty, semantic paraphasia, and naming difficulty. In addition, the types of pragmatic impairments found are repeating ideas, speaking too loudly, talking excessively at inappropriate times, and deviating from the topic. These findings have important implications for healthcare professionals and caregivers who work with people with Alzheimer's disease. By understanding the specific language impairments experienced by people with this condition, they can develop effective communication strategies that take into account the person's individual needs and abilities. Furthermore, more people can help to support the sufferer of Alzheimer's disease and enhance their well-being and social connections.